Determinan Pendapatan Petani Kopi: Analisis Regresi Logistik di Kabupaten Toraja Utara - Syam, Siti Hardiyanti; Tenriawaru, A. Nixia; Ampangallo, Riswa (Jurnal Sosial Ekonomi Pertanian, 2025)
This study aims to analyze the factors influencing coffee farmers’ income in Buntu Pepasan Subdistrict, North Toraja Regency. A binary logistic regression method was employed with 100 respondents selected using the Lemeshow formula. The dependent variable was farmers’ income, categorized as high or low, while the independent variables included fifteen factors, such as land size, land productivity, number of coffee trees, production costs, coffee bean quality, coffee price, certification and quality standards, weather conditions, and other related factors. The results reveal that eight variables have a positive and significant effect on farmers’ income: land size, land productivity, number of coffee trees, production costs, coffee bean quality, coffee price, certification and quality standards, and weather conditions. Conversely, two variables—access to credit and capital, and pest and disease attacks—show a negative effect. The remaining four variables were found to have no significant impact. The Nagelkerke R Square value of 71.2% indicates that the model effectively explains most variations in farmers’ income. These findings highlight that improving farmers’ income relies not only on increasing production but also on enhancing product quality and strengthening institutional management, such as certification. The results provide a scientific basis for formulating policies that focus on improving productivity, strengthening quality standards and certification, enhancing financing systems, and developing pest and disease control strategies. Ultimately, this approach can boost the competitiveness of Toraja coffee and strengthen Indonesia’s position in the global coffee market.